GAGA can mediate enhancer function in trans by linking two separate DNA molecules. - Mahmoudi, T.; Katsani, K.R.; Verrijzer, C.P. (The EMBO Journal, 2002)
Enhancers have been defined as cis-acting DNA sequences that stimulate transcription from a linked promoter in a distance- and orientation-independent manner. How enhancers activate gene transcription over vast chromosomal distances within metazoan genomes remains poorly understood. Here, we show that the transcription factor GAGA can stimulate transcription by linking an enhancer to its cognate promoter. Strikingly, in addition to facilitating activation by a remote enhancer in cis, GAGA can direct activation of a promoter by an enhancer located on a separate DNA molecule. Enhancer function in trans is critically dependent on POZ domain-mediated GAGA oligomerization, enabling GAGA to bind two DNA molecules simultaneously. Transcriptional activation by an enhancer functioning in trans was observed both in transfected cells and in reconstituted transcription reactions. We propose that GAGA facilitates long-range activation by providing a protein bridge that mediates enhancer-promoter communication.